2011
DOI: 10.1148/radiol.10092367
|View full text |Cite
|
Sign up to set email alerts
|

Functional Imaging of the Pelvic Floor

Abstract: The clinical treatment of patients with anorectal and pelvic floor dysfunction is often difficult. Dynamic cystocolpoproctography (DCP) has evolved from a method of evaluating the anorectum for functional disorders to its current status as a functional method of evaluating the global pelvic floor for defecatory disorders and pelvic organ prolapse. It has both high observer accuracy and a high yield of positive diagnoses. Clinicians find it a useful diagnostic tool that can alter management decisions from surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 84 publications
0
58
0
2
Order By: Relevance
“…Each participant underwent a DCP per the following protocol [4,6,17,18]. Instruct patient to retain the suppository for at least 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each participant underwent a DCP per the following protocol [4,6,17,18]. Instruct patient to retain the suppository for at least 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Dynamic colpocystodefecography began at rest and continued sequentially through the straining, voiding, and defecation phases. In older patients and in patients with fecal soiling, it has been suggested that the squeeze sequence done first and the strain sequence eliminated so insure a diagnostic functional sequence [6]. To avoid bladder compression, rectal filling was performed after the voiding phase in patients who exhibited rectoceles during the physical examination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Defaecatory imaging may be poorly tolerated and findings should be interpreted with caution. [10][11][12] Integrated total pelvic ultrasound (endoanal, transvaginal, transperineal) 13 allows dynamic multicompartmental pelvic floor assessment with simultaneous endoanal assessment of the anal sphincter complex and is cheap, safe, portable and well tolerated. 12,14,15 While treatment options for pelvic floor defaecatory dysfunction are continually developing, the assessment algorithm also requires refinement.…”
Section: Introductionmentioning
confidence: 99%